Short Communication: Biology and distribution of Parnassius apollo (Linnaeus, 1758) a rare species in Mordovia Republic, Russia (Biodiversitas Journal of Biological Diversity, 2018)
Ruchin AB, Grishutkin GF. 2018. Short Communication: Biology and distribution of Parnassius apollo (Linnaeus, 1758) a rare species in Mordovia Republic, Russia. Biodiversitas 19: 431-436. There are three isolated populations of Parnassius apollo in Mordovia. The population, found in Mordovia Nature Reserve, is in a sad state and requires urgent protection measures. The second largest population lives in Bolshie Berezniki district. Butterflies from this population are locally found on glades, cuttings, floodplain meadows. It has fragmentized (mosaic) structure of records and a low number of adults. The largest population inhabits Smolny National Park. Irruption typically occurs in this population every few years. The most significant negative impact on the population of Apollo in Mordovia is caused by overgrowing of habitats by small-leaved forests, fragmentation of landscapes, isolation of populations. Data on the number of butterflies and the species composition of fodder plants for the imago of Apollo are given.
Keywords: Abundance; butterflies; ecology; Mordovia Republic; Parnassius apollo; rare species